1976
DOI: 10.1159/000175687
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake, Dietary Supplements and Survival Time of Scorbutic Guinea Pigs

Abstract: Manual presentation of a liquid scorbutogenic diet permitted a more complete characterisation of the terminal stages of scurvy in guinea pigs. A bioflavonoid preparation from orange peel, previously shown both to increase the tissue concentrations of ascorbic acid and to stimulate the growth of hypovitaminotic C guinea pigs, had no influence on the survival time of scorbutic guinea pigs. Tetrahydrofolic acid, reported to possess 40 % of the activity of ascorbic acid in the protocollagen proline-hydroxylase sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…There are indications that the prevention of scurvy as traditionally definedis not the only involvement of AA in the mammalian body. Tetrahydrofolic acid, which has 43 % of the activity of AA in promoting protocollagen proline hydroxylase activity, is ineffective in prolonging the life-span of scorbutic guinea-pigs (Davies et al 1976). Evidence of this type, together with other experimental and clinical reports, could be interpreted as indicating that AA has extra-antiscorbutic functions.…”
Section: Extra-antiscorbutic Involvementsmentioning
confidence: 97%
See 1 more Smart Citation
“…There are indications that the prevention of scurvy as traditionally definedis not the only involvement of AA in the mammalian body. Tetrahydrofolic acid, which has 43 % of the activity of AA in promoting protocollagen proline hydroxylase activity, is ineffective in prolonging the life-span of scorbutic guinea-pigs (Davies et al 1976). Evidence of this type, together with other experimental and clinical reports, could be interpreted as indicating that AA has extra-antiscorbutic functions.…”
Section: Extra-antiscorbutic Involvementsmentioning
confidence: 97%
“…Cholesterol metabolism: Guinea-pig studies haveproduced some evidence of a cholesterol-AA relationship. Chronic hypovitaminosis C resulted in raised tissue levels of cholesterol; loading guineapigs with dietary cholesterol increased the excretion of AA metabolites; and tissue saturation with AA protected guinea-pigs against the toxic effects of high dietary cholesterol (Ginter 1974(Ginter , 1975Hughes 1976Hughes , 1977. These findings are all consistent with Ginter's proposition that AA is involved in the conversion of cholesterol to cholic acidpossibly in one or more of the hydroxylations involved in the conversion.…”
Section: Extra-antiscorbutic Involvementsmentioning
confidence: 99%
“…It is well established, in these species, that a lack of vitamin C in the diet causes all the known symptoms of scurvy, such as listlessness, bleeding gums and nose, loss of teeth (Fig. 9.3 ), deterioration of articulations, brittle bones, and, eventually, death (Davies et al 1976 ;Kipp et al 1996 ;Weinstein et al 2001 ) . Cueto et al ( 2000 ) showed that capybaras also require exogenous vitamin C for survival and that the level of this enzyme cofactor strongly affects the reproductive success of this species in captivity.…”
Section: Scurvymentioning
confidence: 99%